Flavonoid metabolism is involved in regulating the growth of winter wheat upon rehydration - Liu, Xuejing; Yin, Baozhong; Shang, Chong; Bao, Xiaoyuan; Wang, Li; Wang, Tao; Zhen, Wenchao (Frontiers in Plant Science, 2026)
IntroductionExtensive research has been conducted on water- limited irrigation strategies and yield component variations in winter wheat (Triticum aestivum L.). However, limited understanding exists regarding the nuanced responses of winter wheat canopies and gene expressions to rehydration events.MethodsA field investigation was carried out throughout the winter wheat growing season from 2018 to 2020. Four distinct irrigation schedules were implemented, with water supplementation carefully synchronized with irrigation timing to match the appearance of the third, fourth, fifth, and sixth leaves. Further investigation into the molecular mechanisms of winter wheat rehydration using RNA- seq and ultra- performance liquid chromatography- mass spectrometry (UPLC- MS).Results and discussionOur findings show that delayed rehydration results in reduced total water use across all treatment groups during the reproductive growth period, especially from jointing to flowering. A consistent pattern of reduction was observed in leaf area index (LAI), biomass at maturity (BAM), and plant height as rehydration was progressively delayed. The analysis found no statistically significant differences in phenotypic traits among winter wheat at the four- leaf stage before irrigation. In contrast, delaying rehydration until the fifth- leaf stage in spring had a noticeable impact on phenotypic traits. Implementing delayed rehydration at the four- leaf stage increased grain yield by 8. 31% to 51.23. 23%, mainly through three key yield components: more spikes, optimized grains per spike, and higher 1000- grain weight. Interestingly, the increase in 1000- grain weight was inversely related to total grain quantity after postponed rehydration. Transcriptomic and metabolomic analyses showed that postponed rehydration was associated with flavonoid biosynthesis pathways. Notably, the gene related to dihydrokaempferol- known to be involved in phenylpropanoid, flavonol, and flavone biosynthesis- showed a significant positive correlation with naringenin, chrysin, taxifolin, and prunin. Chlorogenic acid and luteolin also exhibited strong positive correlations with various agronomic traits, such as kernel number and 1000- grain weight. These results suggest the presence of a potential molecular regulator at a critical developmental stage, offering new insights into the mechanisms influencing crop yield under water- restricted irrigation conditions.